Fractionation of chain walking polyethylene and elucidation of branching, conformation and molar mass distributions. Issue 1 (2nd January 2021) - Plüschke, Laura; Ndiripo, Anthony; Mundil, Robert; Merna, Jan; Pasch, Harald; Lederer, Albena
Abstract: State-of-the-art liquid interaction chromatography (IC) allows separation of macromolecules according to chemical composition (CC), functionality or molecular topology in contrast to size-based approaches such as size exclusion chromatography (SEC), which has its limitations in distinguishing chemical structures. Yet, for macromolecules with multivariate molecular distributions, online identification and characterization of distinct components in bulk samples is a considerable challenge. A useful approach to narrow down the complexity of a given sample is preparative molar mass fractionation (pMMF) that provides fractions in mg or g scale, which can be subjected to further advanced analysis to elucidate the physical and structural properties of the sample. In this study, novel chain-walking polyethylenes (CWPE), which differ substantially in macromolecular architecture, are fractionated using pMMF. Using IC in temperature and solvent gradient modes (TGIC, SGIC), the pMMF fractions are separated according to branching topology. Quadruple-detector high temperature SEC is carried out to determine the physical properties and study the MM-dependent structural transformation of CWPE. A detailed branching analysis was carried out by means of nuclear magnetic resonance. Two-dimensional liquid chromatography (LC) hyphenating IC and SEC provides comprehensive bivariate correlations between MM and molecular topology.